Recombinaciones y fuentes originales como probadores en un primer ciclo de selección recurrente recíproca de maíz - Gutierrez G., Mario (Instituto Interamericano de Ciencias Agrícolas (IICA), 2025)
corn lines were tested in crosses with the original variety and then recombinations Results in both years indicate that the yields of the crosses to the recombination exce-eded significantly that from crosses to the original variety Results suggest a greater importance of the additive action of yield regulating genes The practice of alternating the breeding of both populations could be important in sub-sequent cycles of this method of selection.